Implementation of accounting curriculum and learning program at vocational school in Bandung - Melvin Christian Abimanyu; Keisha Azahra; Vyanara Aulyadisha; Gina Fadillah (Curricula: Journal of Curriculum Development, 2025)
The accounting curriculum in vocational schools requires unique analysis because of problems adapting learning materials to industry needs and limitations in applying practice-based learning methods. This study aims to analyze the implementation of the Kurikulum Merdeka in accounting vocational programs relevant to the world of work in the era of globalization. The research uses a qualitative approach with interviews and observations as data collection methods. Data sources come from the Deputy Principal for Curriculum and Accounting Teachers. The results showed that implementing the Kurikulum Merdeka has provided positive results, primarily through project-based and problem-based learning approaches that encourage students to think critically, creatively, and innovatively. Despite facing various challenges, the overall implementation of this curriculum creates relevant and innovative learning. It supports the development of student competencies so that they can compete in the world of work. More detailed policy support is needed to ensure the sustainability and strengthening of the Kurikulum Merdeka implementation in competency-based education in the era of globalization.   Abstrak Kurikulum akuntansi di SMK memerlukan analisis khusus sebab adanya permasalahan dalam menyesuaikan materi pembelajaran dengan kebutuhan industri dan keterbatasan dalam penerapan metode pembelajaran berbasis praktik. Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum Merdeka pada program kejuruan akuntansi yang relevan dengan kebutuhan dunia kerja di era globalisasi. Penelitian menggunakan pendekatan kualitatif dengan wawancara dan observasi sebagai metode pengumpulan data. Sumber data berasal dari Wakil Kepala Sekolah bidang Kurikulum dan Guru Akuntansi. Hasil penelitian menunjukkan bahwa penerapan Kurikulum Merdeka telah memberikan hasil positif, terutama melalui pendekatan pembelajaran berbasis proyek dan berbasis masalah yang mampu mendorong peserta didik berpikir kritis, kreatif, dan inovatif. Meski menghadapi berbagai tantangan, penerapan kurikulum ini secara keseluruhan menciptakan pembelajaran yang relevan dan inovatif, serta mendukung pengembangan kompetensi peserta didik supaya dapat bersaing di dunia kerja. Dukungan kebijakan yang lebih terperinci diperlukan untuk memastikan keberlanjutan dan penguatan implementasi Kurikulum Merdeka dalam pendidikan berbasis kompetensi di era globalisasi. Kata Kunci: akuntansi; kurikulum; program pembelajaran; SMK